Adjuvant chemotherapy may improve long-term outcomes in stage IB non-small cell lung cancer patients with previous malignancies: A propensity score-matched analysis - Zhou, Ke; Zhao, Yaqin; Liang, Linchuan; Cao, Jie; Lin, Huahang; Peng, Zhiyu; Mei, Jiandong (Frontiers in Oncology, 2022)
Background: Routine administration of adjuvant chemotherapy for stage IB non-small cell lung cancer (NSCLC) remains controversial. To our knowledge, no available studies have assessed the outcomes of chemotherapy in patients with stage IB NSCLC who had prior malignancies. Methods: Patients with pathological stage IB NSCLC who underwent surgery between 2004 and 2015 were identified from the SEER database. The patients were categorized into chemotherapy and observation groups based on whether they received adjuvant chemotherapy. Propensity score matching was performed to reduce confounding bias and Kaplan-Meier curves and log-rank tests were used to compare overall survival (OS) and cancer-specific survival (CSS) between the two groups. Subgroup analyses of the matched cohorts were then conducted to evaluate the relationship between clinical features and chemotherapy. Results: A total of 894 eligible patients were identified; 90 (10.1%) patients received postoperative chemotherapy. Patients who received adjuvant chemotherapy obtained obvious OS benefits compared with those who received observation alone (HR=0.68, 95% CI: 0.48-0.97, P=0.031). In addition, the 5-year OS rate and median OS time in the chemotherapy groups were higher and longer, respectively. Although chemotherapy offered no obvious benefits for CSS (HR=0.80, 95% CI: 0.57-1.14, P=0.35), patients who received chemotherapy showed a better 5-year CSS rate. On subgroup analyses, a chemotherapy advantage was observed in advanced age (≥65 years, HR=0.62, 95% CI: 0.38-0.99, P=0.045). The same chemotherapy advantages were observed in patients diagnosed with higher histological grades (poorly differentiated to undifferentiated) (HR=0.56, 95% CI: 0.33-0.96, P=0.033) and tumor sizes >3.1–4 cm (HR=0.57, 95% CI: 0.37-0.87, P=0.010). Interestingly, NSCLC patients with previous malignancies originating from the kidney and bladder (HR=0.34, 95% CI: 0.12-0.99, P=0.049) showed a chemotherapy advantage. The same chemotherapy advantages were observed in patients diagnosed with NSCLC within 3 to 5 years after prior cancers (HR=0.39, 95% CI: 0.16-0.98, P=0.044) and with localized SEER stage of prior cancers (HR=0.49, 95% CI: 0.29-0.86, P=0.012). Conclusion: These findings indicate that adjuvant chemotherapy may improve long-term outcomes for stage IB NSCLC patients with previous malignancies. It is recommended that physicians consider the clinical features of previous cancers when making adjuvant chemotherapy decisions for these patients.